THE ROLE OF OPERATIONAL CAPABILITIES IN TRANSFORMING LONG-TERM PRODUCTION COSTS AND PLANTATION INVESTMENT INTO SUSTAINABLE PRODUCTIVITY : EVIDENCE FROM GAYO ARABICA COFFEE AGRIBUSINESS - Devi Andriyani; Ichsan; Hijri Juliansyah; Ratna (CV. Radja Publika, 2026)
Sustainable productivity has become a strategic issue in the development of Gayo Arabica coffee agribusiness due to increasing production costs, the need for plantation investment, and the growing demand for efficient and sustainable farming practices. This study aims to examine the effects of long-term production costs and plantation investment on sustainable productivity through operational capabilities in the Gayo Arabica coffee agribusiness sector in Aceh, Indonesia. A quantitative approach with an explanatory research design was employed. Data were collected through a survey of Gayo Arabica coffee farmers using a structured Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that long-term production costs and plantation investment have positive and significant effects on operational capabilities. Furthermore, both variables positively and significantly influence sustainable productivity. Operational capabilities also have a positive and significant effect on sustainable productivity and mediate the relationships between long-term production costs, plantation investment, and sustainable productivity. These findings suggest that improvements in coffee productivity are not determined solely by the amount of production costs and investments incurred, but also by farmers’ ability to effectively manage resources, technology, and operational processes. This study reinforces the Resource-Based View and Dynamic Capability Theory by highlighting the critical role of operational capabilities as a mechanism for transforming resources into sustainable performance. Practically, the findings provide valuable insights for policymakers, cooperatives, and agribusiness stakeholders in formulating strategies to enhance the sustainable productivity of Gayo Arabica coffee through increased investment and the development of farmers’ operational capabilities.